Analisis Sengketa Pertikaian Antara Rusia Dan Ukraina - Simatupang, Rosinta Paulina Br.; Siregar, Victor Tongam Museka; Husna, Lenny (Prosiding, 2024)
Ukraine's entry into NATO has sparked conflict, shaken global politics and international markets, and brought new challenges to international relations. The impact is predicted to be felt in the long term across the world economy, as explained in Champbell's causality theory. The Russian invasion of Ukraine on 24 February 2022 became a global event of widespread impact, raising internal political tensions in Ukraine and Russia. In Ukraine, political polarization has occurred between NATO supporters and pro-Russia, with the government imposing sanctions on Russian supporers. In Russia, freedom of expression is restricted, and cyber attacks on Ukrainian infrastructure, deepening the dimension of the conflict. The economic impact is severe, with Ukraine undergoing international isolation and Russia facing economic sanctions as well as falling oil prices as a result of a boycott of imports from the United States and its allies. Food deficits also occurred in some regions due to dependence on imports of wheat and oil from Russia and Ukraine. Efforts to resolve the conflict have been made, such as a UN resolution calling for an end to Russian attacks on Ukraine as well as diplomatic efforts by various countries and international organizations, including Indonesia, Turkey, and France. Thus, although the conflict continues, hope lies in diplomatic efforts to bring peace and stability back to the region. The advice that can be given is the need for intensive diplomatic efforts and global coordination to alleviate tensions and mitigate the negative economic impact. The protection of human rights and the principles of international law must also be the focus in responding to this conflict. With a holistic approach and inter-state cooperation, it is expected that the conflict can be resolved peacefully and provide long-term stability for the region and the world.